Uncoupling VEGFA Functions in Arteriogenesis and Hematopoietic Stem Cell Specification - Leung, A; Ciau-Uitz, A; Pinheiro, P; Monteiro, R; Zuo, J; Vyas, P; Patient, R; Porcher, C (2013)
VEGFA signaling is critical for endothelial and hematopoietic stem cell (HSC) specification. However, blood defects resulting from perturbation of the VEGFA pathway are always accompanied by impaired vascular/arterial development. Because HSCs derive from arterial cells, it is unclear whether VEGFA directly contributes to HSC specification. This is an important question for our understanding of how HSCs are formed and for developing their production in vitro. Through knockdown of the regulator ETO2 in embryogenesis, we report a specific decrease in expression of medium/long Vegfa isoforms in somites. This leads to absence of Notch1 expression and failure of HSC specification in the dorsal aorta (DA), independently of vessel formation and arterial specification. Vegfa hypomorphs and isoform-specific (medium/long) morphants not only recapitulate this phenotype but also demonstrate that VEGFA short isoform is sufficient for DA development. Therefore, sequential, isoform-specific VEGFA signaling successively induces the endothelial, arterial, and HSC programs in the DA.